Right ventricular failure: Current strategies and future development - Monteagudo-Vela, María; Tindale, Alexander; Monguió-Santín, Emilio; Reyes-Copa, Guillermo; Panoulas, Vasileios (Frontiers in Cardiovascular Medicine, 2023)
Right heart failure can be defined as a clinical syndrome consistent of signs and symptoms of heart failure resulting from right ventricular dysfunction. Function is normally altered due to three mechanisms: pressure or volume overload, or a decrease in the contractility due to ischaemia, cardiomyopathy or arrythmias. Diagnosis is based in early suspicion using a combination of echocardiographic, laboratory and hemodynamic parameters, and clinical risk assessment. Treatment includes medical management, mechanical assist devices and transplantation if recovery is not observed. Distinct attention to special circumstances such as left ventricular assist device implantation should be sought. The future is moving towards new therapies, both pharmacological and device centered. Immediate diagnosis and management of RV failure, including mechanical circulatory support where needed, alongside a protocolized approach to weaning is the only way to successfully manage right ventricular failure.